2021
DOI: 10.3389/fneur.2021.634945
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Trigeminal Neuralgia Caused by Sole Arterial and Venous Compression: Clinical Features and Surgical Outcomes From 222 Cases

Abstract: Background: Compared with trigeminal neuralgia (TN) caused by arterial neurovascular conflict (NVC), the clinical characteristics and managements for TN with venous NVC are not well-established. This study aims to comparatively summarize the clinical features and surgical outcomes of microvascular decompression (MVD) for patients with TN caused by sole arterial and venous compression, with a particular focus on the morphological features of posterior cranial fossa (PCF).Methods: A total of 222 patients with TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
(54 reference statements)
1
11
0
Order By: Relevance
“…The other studies that have mentioned DR include Wang et al and Shi et al (9,25), in which they reported a DR rate of VO cases was higher than the rate of OA cases. Li et al ( 12) compared 45 patients with typical presentations and 17 patients with atypical presentations.…”
Section: Discussionmentioning
confidence: 97%
“…The other studies that have mentioned DR include Wang et al and Shi et al (9,25), in which they reported a DR rate of VO cases was higher than the rate of OA cases. Li et al ( 12) compared 45 patients with typical presentations and 17 patients with atypical presentations.…”
Section: Discussionmentioning
confidence: 97%
“…Venous compression in TN has been shown to produce a more intractable pain phenotype compared with cases implicating arteries. In a 2021 study by Wang et al 19 investigating differences in outcomes after an MVD, both short-term and long-term pain outcomes were worse for patients with sole venous compression. In particular, 52.9% of 34 patients with sole venous compression experienced insufficient pain relief after their MVD, compared with 15.4% of 188 patients with sole arterial compression.…”
Section: Discussionmentioning
confidence: 99%
“…A similar result was found when reassessed at a more long-term follow-up interval. 19 In addition, morphological changes to the trigeminal nerve in TN cases have been found not only to differ based on the identity of the compressive vessel but also to be predictive of postoperative pain relief after MVD. 12…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 12 ] The therapeutic effect of surgery is well established for cases caused by arterial compression; microvascular decompression cures the disease in 85% of cases. [ 14 ] In contrast, no surgical strategy has been established for cases without obvious arterial compression. [ 2 ] We present a case of TN without arterial compression in a patient on hemodialysis.…”
Section: Introductionmentioning
confidence: 99%